"Ethnic-religious conflict and 'people-to-people' dialogue in Sudan : a theological evaluation of Sudan Presbyterian Evangelical church's Mission on reconciliation" : empirical case study - Weran, Aida N. (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.